Engineering, Characterization, and Biological Evaluation of an Antibody Targeting the HGF Receptor - Desole, Claudia; Gallo, Simona; Vitacolonna, Annapia; Vigna, Elisa; Basilico, Cristina; Montarolo, Francesca; Zuppini, Francesca; Casanova, Elena; Miggiano, Riccardo; Ferraris, Davide Maria; Bertolotto, Antonio; Comoglio, Paolo Maria; et al. (Frontiers in Immunology, 2021)
The Hepatocyte growth factor (HGF) and its receptor (MET) promote several physiological activities such as tissue regeneration and protection from cell injury of epithelial, endothelial, neuronal and muscle cells. The therapeutic potential of MET activation has been scrutinized in the treatment of acute tissue injury, chronic inflammation, such as renal fibrosis and multiple sclerosis (MS), cardiovascular and neurodegenerative diseases. On the other hand, the HGF-MET signaling pathway may be caught by cancer cells and turned to work for invasion, metastasis, and drug resistance in the tumor microenvironment. Here, we engineered a recombinant antibody (RDO24) and two derived fragments, binding the extracellular domain (ECD) of the MET protein. The antibody binds with high affinity (8 nM) to MET ECD and does not cross-react with the closely related receptors RON nor with Semaphorin 4D. Deletion mapping studies and computational modeling show that RDO24 binds to the structure bent on the Plexin-Semaphorin-Integrin (PSI) domain, implicating the PSI domain in its binding to MET. The intact RDO24 antibody and the bivalent Fab2, but not the monovalent Fab induce MET auto-phosphorylation, mimicking the mechanism of action of HGF that activates the receptor by dimerization. Accordingly, the bivalent recombinant molecules induce HGF biological responses, such as cell migration and wound healing, behaving as MET agonists of therapeutic interest in regenerative medicine. In vivo administration of RDO24 in the murine model of MS, represented by experimental autoimmune encephalomyelitis (EAE), delays the EAE onset, mitigates the early clinical symptoms, and reduces inflammatory infiltrates. Altogether, these results suggest that engineered RDO24 antibody may be beneficial in multiple sclerosis and possibly other types of inflammatory disorders.